THE KAIDUN METEORITE: CLASTS OF ALKALINE-RICH FRACTIONATED MATERIALS - Ivanov A.V.; Kononkova N.N.; Yang S.V.; Zolensky M.E. (My University, 2003)
Clasts of alkaline (the second find in meteorites) and subalkaline rocks were found in the Kaidun meteorite. One of them (#d4A) is a large crystal of albite with inclusions of fluorapatite, arfvedsonite, aenigmatite, and wilkinsonite. The two latter minerals were previously unknown in meteorites. Another clast (#d[3–5]D) has a melt crystallization texture of mainly feldspar (oligoclase) composition and contains relict grains of both high-Ca and low-Ca pyroxene and fluorapatite. The mineralogical characteristics of these clasts suggest a genetic relationship and an origin from the same parent body. The textural and mineralogical characteristics of the clasts indicate origin by extensive igneous differentiation. Such processes most likely took place in a rather large differentiated body. The material of clast #d(3–5)D is similar in some mineralogical respects to basaltic shergottites.